Role of Communication in the Process of a Better Awareness of Environmental and Health Risks Related to the Use of Pesticides in Off-Season Vegetable Crops in Burkina Faso: Case of the Boulmiougou Dam in Arrondissement N°6, Urban Commune from Ouagadougou - COMPAORE, Jérôme (Advances in Social Sciences Research Journal, 2022)
The cultivation of off-season crops is encouraged in Burkina Faso as part of its development policy and also to address the food shortage experienced by the country due to its Sahelian location with capricious rainy seasons. Thus, this activity has been intensified around water reservoirs and marshy areas to overcome this food shortage. However, market gardeners are faced with damage caused by pests, which forces them to make extensive use of pesticides. The present study consisted of a process of communication for behavioral change, to offer modern tools (coaching, awareness) for the benefit of market gardeners in the commune of Boulmiougou. This approach is part of a dynamic to familiarize them with good knowledge of pesticides in their diversity, and especially their use in the required scientific standards and in the preservation of our living environment.